POLITICAL REFORM OF NATIONAL ECONOMIC LAW (Analysis of the Impact of Globalisation on National Investment Law) - Surizki Febrianto (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2023)
The objective of this study is to investigate the relationship between investment law and state sovereignty, and subsequently formulate a framework for future national investment law policies aimed at promoting economic growth and safeguarding sovereignty. The present study is characterized as normative in its methodology, employing both a statutory and conceptual approach. The findings indicate that investment plays a significant role in enhancing both the economy and employment expansion. Governments globally are engaged in a competitive effort to establish an improved business climate that facilitates investment activities. However, it is imperative to restrict this endeavor and prioritize domestic capital, as evidenced by the 1966 MPRS Decree. This directive provides guidance to Indonesian policymakers that foreign investment or aid should not be disregarded for its role in developing the struggling Indonesian economy. Nevertheless, it is crucial to first rely on the potential of domestic resources as a means of generating development funds. This approach ensures that the availability of foreign funding sources does not lead to dependence on external parties. Furthermore, foreign sources of funds must be utilized for the benefit of the domestic economy.  Foreign investment in Indonesia must also be subjected to limitations in this context